Tools from Trash: Recycling pathways and use cases for rapid tooling - Frohn-Sörensen Peter; Schiller Michael; Reinicke Tamara; Engel Bernd (MATEC Web of Conferences)
Modern society has tackled final limitations of earth-bound resources which is why presently large efforts are being conducted to preserve and reuse the existing materials that are already being used. Out of the so called six/nine R principles, recycling is one of the methods to achieve the goal of resource conservation. Particularly crucial to the application of reclaimed materials is to understand changing mechanical properties as well as the impact on component utilization. The present study suggests applying recycled materials for manufacturing tools such as sheet metal forming dies. A deep drawing tool is fabricated from recycled polymer waste material and compared to a conventional steel tool as baseline. A series of sheet metal pieces are fabricated on both diesets and compared by means of process force evolution over progression as well as product geometry. The approach demonstrates the application potential of recycled materials for tools and provides insides on a highly altered tool material stiffness.